2009
DOI: 10.1080/00222930903383529
|View full text |Cite
|
Sign up to set email alerts
|

A new species of the genusEuseiusWainstein (Acari: Phytoseiidae) from France

Abstract: The identity of specimens belonging to the genus Euseius found on several trees in France is investigated. Previous molecular and morphological analyses have shown that the new species herein described is different from Euseius stipulatus. Among the 187 species belonging to the genus Euseius, four of them (Euseius querci, Euseius amissibilis, Euseius kirghisicus and Euseius longiverticalis) seem to be morphologically close to this new species. However, none were very similar. This paper reports the description… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
3
23
0
1
Order By: Relevance
“…Distribution: E. gallicus has been reported in Tunisia (Kreiter et al, 2010), Belgium, France, Germany, the Netherlands and Turkey (Tixier et al, 2009;Döker et al, 2014b). In this research, it was found together with Xenotarsonemus sp., T. goetzi and B. mali on C. annuum.…”
Section: Euseius Gallicus Kreiter and Tixier 2010supporting
confidence: 55%
“…Distribution: E. gallicus has been reported in Tunisia (Kreiter et al, 2010), Belgium, France, Germany, the Netherlands and Turkey (Tixier et al, 2009;Döker et al, 2014b). In this research, it was found together with Xenotarsonemus sp., T. goetzi and B. mali on C. annuum.…”
Section: Euseius Gallicus Kreiter and Tixier 2010supporting
confidence: 55%
“…Euseius gallicus Kreiter and Tixier in Tixier et al 2010: 242. This species was described from Southern France (Tixier et al 2010). It had also been recorded from Tunisia, Belgium, Germany, the Netherlands, and Turkey (Kreiter et al 2010;Döker et al 2014) and recently from Slovenia (Kreiter et al 2020a).…”
Section: Euseius Gallicus Kreiter and Tixiermentioning
confidence: 91%
“…Without pollen, the predatory mites hardly survived, indicating that they also hardly attack E. americanus on plants. The predatory mite E. gallicus is relatively new (Tixier et al 2010) and was found to occur on greenhouse rose plants (Döker et al 2014). In this crop it is now advised to use together with pollen for controlling thrips and whiteflies because of its good performance on pollen Put et al 2016).…”
Section: Discussionmentioning
confidence: 99%